PENGEMBANGAN MODUL IPA BERBASIS EKOSISTEM PESISIR TERHADAP PEMAHAMAN KONSEP KEANEKARAGAMAN HAYATI SISWA KELAS V SD N 9 LANGSA - Permata Sari, Ayu; Mahlianurrahman; Maisarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low mastery of science concepts in IPAS learning among fifth-grade students at SD N 9 Langsa on the topic of biodiversity, as indicated by an average pretest score of 41.82%. This low achievement was caused by learning that relied heavily on textbooks, abstract presentation of materials, and limited use of the coastal environment as a learning resource. This study aimed to develop a coastal ecosystem-based science learning module and assess its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The trial was conducted with fifth-grade students at SD N 9 Langsa. Data collection techniques included expert validation, teacher and student response questionnaires, and concept mastery tests in the form of pretests and posttests. The results showed that the developed module integrated the coastal ecosystem context with the local wisdom value of Panglima Laot. The module achieved a very high level of validity based on assessments by material experts (100%), instructional design experts (100%), and language experts (91.6%). The practicality level was also very high, with teacher responses of 85.7% and student responses of 91.5%. Furthermore, the module was proven effective in improving students’ concept mastery, with an average N-Gain score of 0.8083 (80.83%) and a Wilcoxon Signed-Rank Test significance value of 0.005 (< 0.05). Therefore, the coastal ecosystem-based science learning module is considered feasible for use in IPAS learning in elementary schools.